Advances in web-based GIS, mapping services and applications - Li, Songnian 1963-; Dragicevic, Suzana 1963-; Veenendaal, Bert (CRC Press/Balkema, 2011)
"A detailed look at the field of web-based GIS and mapping services and applications, this book reviews current progress and achievements, while looking forward to future developments. It address issues involved in constant updating of related web and geospatial technologies as well as the revolution of web mapping caused by mainstream IT vendors. The text include coverage of increased interest in geo-spatial information technologies and increasing demand for prompt and effective spatial information services. It highlights applications in business, government services, enterprise computing, and social networking" -- Provided by publisher.